+0  
 
0
357
3
avatar

 Which of the following is equivalent to the expression (9x^2y^3) (12x^-3y^5) (2xy)

A: 23x^-5y8
B: 216y^9
C: -x^-6y^8

D: -216x^-7y^15

 

 A little math question I had for homework I couldn't solve. Any help?

Guest Apr 27, 2017
 #1
avatar+27219 
+1

(9x^2y^3) (12x^-3y^5) (2xy) → (9*12*2)*(x^2*x^-3*x)*(y^3*y^5*y) → 216*(x^[2-3+1])*(y^[3+5+1]) → 216*x^0*y^9 → 216*y^9

.

Alan  Apr 27, 2017
 #2
avatar+94090 
+2

(9x^2y^3) (12x^-3y^5) (2xy)

 

\((9x^2y^3) (12x^{-3}y^5)(2xy)\\ =9x^2y^3* 12x^{-3}y^5*2xy\\ =9*12*2\;x^2 x^{-3}x^1y^3y^5y^1\\ =216\;x^{2+-3+1}y^{3+5+1}\\ =216\;x^{0}y^{9}\\ =216\;y^{9}\\ \)

Melody  Apr 27, 2017
 #3
avatar
0

Opuść nawiasy i zredukuj wyrazy podobne 

 

a) 3(a-5)+4(7+a)
b) 1,5(ab+2)-6(ab-1)
c) -(2x²-y+xy)+2(x²-3y-xy)
d) -3(0,5xy+2x)-5(-3xy-x)

Guest Apr 27, 2017

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.